2014
DOI: 10.1111/epi.12631
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol: Pharmacology and potential therapeutic role in epilepsy and other neuropsychiatric disorders

Abstract: Objective To present a summary of current scientific evidence about the cannabinoid, cannabidiol (CBD) with regards to their relevance to epilepsy and other selected neuropsychiatric disorders. Methods We summarize the presentations from a conference in which invited participants reviewed relevant aspects of the physiology, mechanisms of action, pharmacology and data from studies with animal models and human subjects. Results Cannabis has been used to treat disease since ancient times. Δ9-THC is the major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
608
0
52

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 852 publications
(704 citation statements)
references
References 68 publications
5
608
0
52
Order By: Relevance
“…The 2 major phyto-cannabinoid constituents with central nervous system activity are THC, responsible for the euphoric and mind-altering effects, and CBD, which lacks these psychoactive effects. Preclinical and clinical studies show CBD possesses a wide range of therapeutic properties, including antipsychotic, analgesic, neuroprotective, anticonvulsant, antiemetic, antioxidant, anti-inflammatory, antiarthritic, and antineoplastic properties (see [11,12,[16][17][18][19] for reviews). A review of potential side effects in humans found that CBD was well tolerated across a wide dose range, up to 1500 mg/day (orally), with no reported psychomotor slowing, negative mood effects, or vital sign abnormalities noted [20].…”
Section: Cbd Pharmacology Relevant To Anxiety General Pharmacology Anmentioning
confidence: 99%
“…The 2 major phyto-cannabinoid constituents with central nervous system activity are THC, responsible for the euphoric and mind-altering effects, and CBD, which lacks these psychoactive effects. Preclinical and clinical studies show CBD possesses a wide range of therapeutic properties, including antipsychotic, analgesic, neuroprotective, anticonvulsant, antiemetic, antioxidant, anti-inflammatory, antiarthritic, and antineoplastic properties (see [11,12,[16][17][18][19] for reviews). A review of potential side effects in humans found that CBD was well tolerated across a wide dose range, up to 1500 mg/day (orally), with no reported psychomotor slowing, negative mood effects, or vital sign abnormalities noted [20].…”
Section: Cbd Pharmacology Relevant To Anxiety General Pharmacology Anmentioning
confidence: 99%
“…Cannabis has a long anecdotal history of use for the treatment of epilepsy, although, confusingly, significant reports of proconvulsant effects are also present in the literature (for a detailed review see [124]). CBD has a more consistent record and has been repeatedly shown to exert anticonvulsant effects in a variety of preclinical models and small, but flawed, clinical trials but the mechanism through which these effects are exerted remains to be determined [124]. Here, we consider the potential role that the pharmacological targets identified in part 1 can play in epilepsy and its symptoms.…”
Section: Epilepsymentioning
confidence: 99%
“…However, exploitation of adenosine agonists as epilepsy treatments has been unsuccessful owing to the very narrow therapeutic window that can result in significant adverse events. In particular, those affecting the cardiovascular system in humans and in animal models, which suggests that direct agonism of A 1 /A 2 receptors by CBD is unlikely and, as such, indirect elevation of local adenosine levels is not only more plausible but could represent a viable mechanism underlying CBD's anticonvulsant effects [124,155].…”
Section: Cbd Receptor Targets In Epilepsymentioning
confidence: 99%
“…Therefore, the preclinical evidence collected so far is highly suggestive of important benefits to be reached in newborns affected by HI encephalopathy with cannabinoid-based therapies, in particular with the nonpsychoactive phytocannabinoid CBD, which appears to be an adequate therapeutic option for the treatment of neonatal and infantile disorders. In fact, CBD has already been formulated as Epidiolex (GWPharma) and received the orphan designation from US and European regulatory agencies for the treatment infantile refractory epilepsies [76]. It may be a good choice for investigating the benefits of cannabinoid-based therapies in neonatal ischemia at the clinical level, alone or in combination with hypothermia, which is the only approved therapeutic strategy for this pathological condition.…”
Section: Cannabinoids and Brain Damage In The Immature Brain: Neonatamentioning
confidence: 99%